The safety and efficiency of benzoyl peroxide for reducing Cutibacterium acnes in the shoulder: An updated systematic review and meta-analysis - Fan, DingYuan; Ma, Jia; Liu, XiaoHua; Zhang, Sheng; Sun, Jin; Li, Yan; Jiang, Bo; Zhang, Lei (Frontiers in Surgery, 2023)
Background: Cutibacterium acnes (C. acnes), as a common pathogen, contributes significantly to infections in shoulder surgery. Prevention of shoulder infection is crucial to improve postoperative functional recovery and reduce costs. This study aimed to perform a systematic review and meta-analysis to assess the safety and efficacy of 5% benzoyl peroxide (BPO) in shoulder to decrease C acnes. Methods: Three electronic databases were searched as follows: PubMed, Embase, and the Cochrane Library databases. Data extraction of this study was performed by two independent reviewers and only level Ⅰ and level Ⅱ studies were included. The outcome data sources of individual studies were pooled. The fixed-effect model was used to determine the meta-analysis. Results: There were five level Ⅰ studies and five level Ⅱ studies. The result showed 5% BPO group had lower risks of rate in positive C. acnes (OR, 0.21[0.15, 0.30], I2=24, p＜0.00001). The pool analysis result showed there was no significant difference in 5% BPO and 5% BPO + clindamycin to reduce C acnes. However, the lower rate of adverse events was significantly in favor of Non-BPO group compared with 5% BPO. Conclusion: BPO could decrease C. acnes for shoulder to prevent infection. However, the combination of BPO and clindamycin did not enhance the effect further.